Enhancing vocational school counseling program supervision through data-driven feedback - Sudibyo, Hanung; Yustiko Prasetya, Yovian (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
This study aims to explore the effectiveness of a data-driven structured feedback mechanism in the supervision of guidance and counseling (BK) programs in vocational high schools (SMK) in Central Java, Indonesia. Using a quasi-experimental design with pretest-posttest control group approach, the study involved 10 vocational high schools, with 5 schools each in the experimental and control groups. The experimental group comprised 5 supervisors and 10 counseling teachers, while the control group had the same number of participants. Results showed a significant improvement in supervisory effectiveness in the experimental group, with a mean difference of 1.25 (p < 0.001), compared to a minimal increase of 0.15 in the control group. The findings highlight the importance of integrating data in educational supervision and contribute to the development of more effective supervision models.